PELAKSANAAN HAK CUTI KARYAWAN DI PT. KHARISMA RANCANGADI PRATAMA (BIGLAND) SAMARINDA DITINJAU DARI UNDANG – UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Romauli Nainggolan (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThe Government has enacted Law Number 13 of the Year 2003 on Manpower. It is intended to guarantee the basic rights of workers and ensure equal opportunity and treatment without discrimination on any ground to realize workers' welfare. In connection with the above description to be more real and in-depth about the implementation of Law No. 13 of 2003 on Employment in the company, this study is limited to employees at PT. Kharisma Rancangadi Pratama Samarinda engaged in the production of making Spring bad.The government should be able to respond to the problems of employment that occur in the community. The government should be more active in conducting counseling and supervision of labor on a regular basis to large companies and small companies so that the employers and workers / laborers can obtain knowledge and information about the employment.